USAHA MEMPERBAIKI KUALITAS GURU DENGAN MENGOPTIMALKAN KOMPETENSI PAEDAGOGIK DAN KOMPETENSI KEPRIBADIAN - admin admin; Khoiril khoiril (Universitas Muhammadiyah Gresik, 2013)
One cause of low morale of our current generation is the low morale of teachers and parents. The tendency of the teacher's task is only to transfer of knowledge regardless of the moral values embodied in science. Learning conditions today are very oriented to the acquisition of the figures as the standardization of the quality of education. There are several factors that lead to teacher personality of